PEMANFAATAN LIMBAH KULIT IKAN LEMADANG MENJADI PRODUK YANG BERNILAI TINGGI DI DESA LABUHAN HAJI - Budiana, I Ketut Satya; Jurnal Wicara; Agustiawan, Romy; Suryani, Bulqis Putri; Putri, I Gusti Ayu Yunita; Amin, Lalu M. Ali Sam’un Al; Mahardika, Chaerisna; Ulfi, Baiq Subbidia; Khotimah, Baiq Khusnul; Ningsih, Baiq Nely Rahma (Jurnal Wicara, 2025)
Labuhan Haji Village is located in East Lombok Regency, precisely at the eastern end of the coast of Lombok Island which has great potential in the field of fisheries. Most residents only use fish meat and let fish waste go to waste. With the theme of Green Economy through the concept of Zero Waste, KKN-PMD students of the University of Mataram Year 2025 carry out mentoring and innovation programs in processing fish skin waste into products of economic value, namely fish skin crackers. This community empowerment effort was carried out at the Dapur Pesisir Fish Processing and Marketing Group (Poklahsar) as a form of commitment to developing fish skin crackers as an innovative new product. The methods applied include socialization, hands-on practice, evaluation, and product finalization through packaging, labeling, and even making promotional videos to reach the digital market. This innovative product has promising market prospects thanks to its distinctive taste, high nutritional value, and environmental friendliness. The program succeeded in improving the community's understanding, skills, and entrepreneurial spirit while contributing to the reduction of waste in coastal areas. The sustainability of this program requires support from the government and related institutions so that innovative products based on fish waste can compete in regional and national markets.